A unique case of inflammatory fibroid polyp in the duodenum of a female adolescent: Case report and literature review. Issue 8 (February 2017) - Calderon, Mauricio Giusti; Caivano, Valéria Campos; Bagnaresi, Sauro; de Oliveira Lira, José Ozório; Raimundo, Rodrigo Daminello; de Abreu, Luiz Carlos; Correa, João Antonio
Abstract: Background: Inflammatory fibroid polyp (IFP) is a very rare benign condition in children that can occur throughout the gastrointestinal tract. It is characterized as a polypoid lesion originating in the submucosa, composed of connective tissue and eosinophilic infiltrate. It is most common in the stomach and in adults between the fifth and seventh decades of life. Its occurrence is unusual in the duodenum. Case Summary: One case of duodenal IFP was described and the literature is reviewed with emphasis on the clinical and pathological features of IFP in children. A case of an IFP in the duodenum of a 13-year-old girl, who presented with abdominal pain, weight loss, vomiting, and constipation. The patient underwent exploratory laparotomy; a stenosing tumor of the third duodenal portion was found. The affected segment was resected and an end-to-end anastomosis between the duodenum and jejunum segment was performed. Immunohistochemically, actin and CD34 were positive, Ki67 was positive in <1% of cells, and the proteins CD117 and S100 were negative. Conclusion: To our best of our knowledge, this is the fourth report of IFP in adolescents, the first in a female's duodenum.